Guest editorial : Special Guest IASAS Edition: Issues and Challenges in Student Affairs and Services Around the World (Journal of Student Affairs in Africa, 2021)
The mission of the International Association of Student Affairs and Services (IASAS) isto serve “as a global advocate for students in higher education, student affairs and services practitioners, and the profession itself” (IASAS, 2017). It seems appropriate that the specialedition of JSAA focuses on issues and challenges in student affairs and services around the world. IASAS was formed from the awareness of and need for a global network for student affairs and services. It was in the mid-90s that the leadership in professional associations and institutions, along with key individuals, began to recognise a need for growth. It was the leadership within IASAS, specifically Roger Ludeman and his colleagues, who pushed for dialogue, connection, and networking around the world. Since its establishment and the recognition of the internationalisation of higher education, we have seen an increase in literature, meetings, presentations, and a general interest in global issues within the field of student affairs and services. Global professional organisations such as IASAS are providing a space for professionals to engage with one another, to share common issues and concerns, and to dialogue with colleagues around the world. Events such as the Global Summits that have taken place over the past few years and other national, regional, and international professional conferences are allowing the sharing of knowledge, ideas, and best practices. Moreover, with journals such as JSAA, the field of student affairs and services is starting to hear more voices ofprofessionals, and learn of both common and new issues and challenges within the fieldaround the world. Due to this growing shift in perspective, this issue highlights a few of those challenges as well as providing reviews of resources available to better our own understandings of student affairs and services around the world, and how we support our students. Authors in this issue as well as scholars are discussing the topic of professionalisation, training ofstudent affairs staff, and the continual emphasis on students. We received submissions fromSouth Africa, Botswana, China, and the USA with a total of five articles and three reviews of seminal works.
Keywords: International Association of Student Affairs and Services; IASAS; JSAA; Student Affairs; South Africa; Botswana; China; USA